PEMBANGUNAN IKN DAN PERGESERAN DISTRIBUSI KEKUASAAN EKONOMI DI INDONESIA: PERSPEKTIF KERUANGAN DAN SISTEM SOSIAL - Kartini; Novi Zaini; Mujiati; Gusmal Hendra; Halimatul Mahmudah; Sumanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Nusantara Capital City (IKN) is a strategic policy aimed at reducing the concentration of development in Java and promoting more balanced regional development in Indonesia. This study analyzes IKN development in the context of shifting economic power distribution from spatial and social system perspectives. The research employs a qualitative method using a library research approach. Data were collected from scholarly articles, books, research reports, and policy documents and analyzed through content analysis. The findings indicate that IKN has the potential to establish a new growth center in East Kalimantan through increased investment, infrastructure development, and stronger regional connectivity. These developments may encourage the redistribution of economic activities that have long been concentrated in Java. From a social perspective, IKN development generates changes in population mobility, urbanization, livelihood structures, and interactions between local communities and newcomers. The project also presents challenges related to socio-spatial inequality, changing land control patterns, and the need for inclusive governance. The study concludes that IKN functions as an instrument of spatial transformation with implications for the distribution of economic power and social systems in Indonesia.